Long noncoding‐RNA component of mitochondrial RNA processing endoribonuclease is involved in the progression of cholangiocarcinoma by regulating microRNA‐217. Issue 7 (28th June 2019) - Tang, Lingyu; Wang, Yuting; Wang, Huishan; Xu, Boming; Ji, Hao; Xu, Guolong; Ge, Xianxiu; Li, Quanpeng; Miao, Lin
Abstract: Cholangiocarcinoma (CCA) is a malignant tumor originating from bile duct epithelium and its incidence is increasing year by year. In recent years, long noncoding RNAs (lncRNAs) have been found to play an important role in the occurrence and progression of malignant tumors. In the present study, for the first time, abnormal expression of lnc‐RNA component of mitochondrial RNA processing endoribonuclease (RMRP) and its possible role in CCA were found. We explored the effects of RMRP on various behaviors of CCA cells in vitro and in vivo. In addition, by second‐generation sequencing, we explored the microRNA expression profiles that RMRP may affect in the HCCC‐9810 cell line. We also validated and explored the role of microRNA‐217 (miR‐217) with high differential expression by in vitro experiments. Our findings indicated that RMRP can play a part in promoting cancer by regulating the expression of miR‐217. RMRP is involved in the progression of CCA and can be a novel indicator of poor prognosis in patients with CCA. Abstract : Lnc‐RMRP is overexpressed in cholangiocarcinoma tissues and cell lines. RMRP may act as an oncogene by regulating downstream microRNAs such as miR‐217.